Remineralizing Potential of Bioactive Glass–Ceramic over White Spot Lesions - Silva, Stéphanie O; Soares, Eduardo J.; Amorim, Ayodele A.; Geng Vivanco, Rocio; Pires-de-Souza, Fernanda C.P. (European Dental Research and Biomaterials Journal, 2023)
Objective This study evaluated the effect of incorporating biosilicate (Bio) particles into experimental toothpaste (ET) on their abrasiveness and remineralization capacity for white spot lesions (WSLs).Materials and Methods Thirty-two fragments of bovine teeth (6 × 6 × 2 mm) were obtained. Initial microhardness (Knoop hardness number [KHN], HMV Microhardness Meter, Shimadzu) and surface roughness (Rugosimeter Surfcorder SE 1700) readouts were performed. Fragments were submitted to a cariogenic challenge to simulate WSLs and then divided into four groups: Control, conventional toothpaste (Colgate Smiles, Colgate-Palmolive Company); ETF, ET with fluoride (carboxymethylcellulose + glycerol + thickening silica + fluoride); ETB, ET with Bio; BS, biosuspension (10 in weight% Bio). Toothpaste treatments were performed through simulated toothbrushing (Pepsodent, MAVTEC, 14,600 cycles). BS was applied by immersion for 8 hours followed by 16 hours in artificial saliva at 37°C for 60 days, totalizing 1,440 cycles. After treatments, final KHN and surface roughness readings were performed, and scanning electron microcopy (SEM) was conducted (Jeol JSM-6610LV) for morphological analysis. Data were analyzed with one-way analysis of variance, Tukey's test (p < 0.05).Results BS produced the least surface roughness change, different (p < 0.05) from all the other groups. ETB caused higher KHN than ETF (p < 0.05). SEM images revealed that ETB and BS resulted in abraded surfaces with deposition of particles.Conclusion ETB resulted in similar abrasiveness to the control group, and it caused higher microhardness than the ETF.Practical Implication Considering its higher KHN, ETB could be considered a proper alternative for the treatment of WSLs.
Keywords: toothpaste; biomaterial; biosilicate; white spot lesion; dental remineralization